Arabic Orthography Instruction and Writing Accuracy among Madrasah Students: Insights for AI-Assisted Language Learning - Emiyiati, Rifka; Kamalia (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2026)
The growing use of AI-assisted language learning highlights the importance of foundational writing competencies in Arabic language education. This study aims to investigate the implementation of Arabic writing instruction, identify students’ writing difficulties, and examine its relevance to AI-assisted language learning. Using a qualitative descriptive approach, the study was conducted at MTs Darul Irsyadiyah Labuhanbatu involving seventh-grade students and an Arabic language teacher. Data were collected through observations, interviews, and documentation and analyzed descriptively. The findings reveal that writing instruction was implemented systematically to improve students’ orthographic accuracy. However, students continued to experience difficulties in distinguishing visually similar Arabic letters, applying harakat accurately, and writing independently. Limited instructional time and insufficient writing practice were identified as major challenges. The study suggests that orthographic competence remains a fundamental prerequisite for effective Arabic writing, even in AI-assisted learning environments where automated feedback and writing support are increasingly available.